First report of Aecidium cantense (potato deforming rust) on Solanum macrocarpon (African eggplant) in Benin. - Beed, Fenton D.; Houessou, J.H.; Kelly, P.; Ezin, V. (Wiley, 2011)
In October 2009, specimens of African eggplant (Solanum macrocarpon) from around Cotonou in southern Bénin initially developed small, smooth swellings on the lower surface of the leaves and yellow-green depressions on upper leaf surfaces. Within seven days, orange to brown pustules with with a diameter 4-10 mm formed on lower leaves. Urediniospores were orange, circular and echinulae, and 15-25 × 20-25 µm in size. The morphological analysis of the isolates confirmed the rust fungus to be A. cantense (GPC accession no. W10327). This is thought to be the first report of A. cantense (potato deforming rust) on African eggplant in Benin.